2022
DOI: 10.3389/fneur.2022.818332
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Diffuse Cerebral Microbleeds in Cerebral Autosomal Recessive Arteriopathy With Subcortical Infarcts and Leukoencephalopathy

Abstract: Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is a hereditary cerebral small vascular disease caused by a homozygous mutation in the high-temperature requirement A serine peptidase 1 (HTRA1) gene. Cerebral microbleeds (CMBs) are increasingly being recognized as neuroimaging findings occurring with cerebrovascular disease and have different etiologies. Mild to moderate CMBs are not unusual in CARASIL, and they are observed to affect cortical and subcortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The exact incidence of microbleeds in CARASIL is poorly documented at present, given the rarity of this condition. [ 24 , 25 ]…”
Section: Causes Of Cmbsmentioning
confidence: 99%
“…The exact incidence of microbleeds in CARASIL is poorly documented at present, given the rarity of this condition. [ 24 , 25 ]…”
Section: Causes Of Cmbsmentioning
confidence: 99%
“…Mild to moderate cerebral microhemorrhages are common in CARASIL patients, but diffuse cerebral microhemorrhages are rare. Wen et al 56 reported a 43-year-old woman whose imaging showed multiple cerebral microhemorrhages in all lobes, the brainstem and the cerebellum. After sequencing, it was found to be a novel mutation in HTRA1, so HTRA1 gene mutation was considered to be associated with cerebral microbleeds.…”
Section: Htra1 Gene Abnormalities and Cerebrovascular Diseasementioning
confidence: 99%